Experimental Study of Bilinear Initiating System Based on Hard Rock Pile Blasting - Yusong Miao; Xiaojie Li; HongHao Yan; Xiaohong Wang; Junpeng Sun (Shock and Vibration)
It is difficult to use industrial explosives to excavate hard rock and achieve suitable blasting effect due to the low energy utilization rate resulting in large rocks and short blasting footage. Thus, improving the utilization ratio of the explosive energy is important. In this study, a novel bilinear initiation system based on hard rock blasting was proposed to improve the blasting effects. Furthermore, on the basis of the detonation wave collision theory, frontal collision, oblique reflection, and Mach reflection during detonation wave propagation were studied. The results show that the maximum detonation pressure at the Mach reflection point where the incident angle is 46.9° is three times larger than the value of the explosive complete detonation. Then, in order to analyze the crack propagation in different initiation forms, a rock fracture test slot was designed, and the results show that bilinear initiating system can change the energy distribution of explosives. Finally, field experiment was implemented at the hard rock pile blasting engineering, and experimental results show that the present system possesses high explosive energy utilization ratio and low rock fragments size. The results of this study can be used to improve the efficiency in hard rock blasting.